Automated Assessment of Student Queries in Redis - Yuliia Prokop (Proceedings of the International Conference on Applied Innovations in IT)
In recent years, the popularity of NoSQL systems has grown significantly due to their flexibility and high performance when working with large volumes of data. Redis is one of the most popular key-value stores actively used in industry and education. However, automated approaches for NoSQL assignment evaluation, especially those involving advanced Redis modules, remain underdeveloped. This paper presents a web-based system for automated assessment of students’ Redis queries, supporting basic structures (e.g., list, sorted set, and hash manipulation) and advanced features (RedisJSON and RediSearch). The system provides instant feedback on syntax errors, enabling students to correct mistakes and resubmit solutions in real-time. A pilot study with 42 master’s students showed that about 78% successfully mastered the basics of Redis on the first try, while only 39% passed advanced assignments. With repeated attempts and targeted feedback, overall success on advanced tasks increased to 76%, highlighting the importance of continuous, automated guidance. The paper also discusses typical errors logged by the system (inconsistent or incorrect key naming, syntax errors when setting key expiration, incorrect index creation or JSON field references, etc.). The results demonstrate that integrating an automated Redis query assessment into educational programs can significantly enhance student engagement and learning efficiency. The flexible and modular design of the proposed system allows easy extension to other NoSQL databases and provides valuable data for instructors to refine teaching materials.